Population and family life education for health, sustainable democracy and nation building: the Nigerian experience (2005)
The need for Nigerian government to promote the health of its citizens, sustain the nascent democracy and mobilize people for nation building cannot be overemphasized. The need becomes necessary, especially at this time when the country is yearning for technological and industrial developments. The nation’s most valuable asset is its population, being the agent and beneficiary of development. The improvement of quality of Ife is vital to national development. Improved quality of Ife is a key concept in the entire process of population and family Ife education (POP/FLE). Therefore, this paper examined the concepts of POP/FLE and its role in promoting health, sustainable democracy and nation building. The paper called for a sustained interest of government in POP/FLE programme in Nigeria.